Mechano‐Responsive Dyes: Observation of Interfacial Damage in a Silk‐Epoxy Composite, Using a Simple Mechanoresponsive Fluorescent Probe (Adv. Mater. Interfaces 10/2017). Issue 10 (May 2017) - Woodcock, Jeremiah W.; Beams, Ryan; Davis, Chelsea S.; Chen, Ning; Stranick, Stephan J.; Shah, Darshil U.; Vollrath, Fritz; Gilman, Jeffrey W.
Abstract : Jeffrey W. Gilman and co‐workers observe interfacial damage in a silk‐epoxy‐composite in article number1601018 . Hundreds of microns inside a silk‐fiber composite, two‐photon fluorescence life‐time imaging and hyperspectral imaging of a damage‐sensing probe (mechanophore), reveals interface debonding, fiber fracture, and chemical reaction with the matrix. Functional groups on the periphery of the fluorescent probe chemically link the fiber and matrix. Stress transfer across the probe's strained spirolactam center activate the probe's fluorescent properties.